KANDUNGAN EKSTRAK DAUN BANTEN (Lannea coromandelica (Houtt.) Merr.) OBAT TRADISIONAL LOMBOK SEBAGAI ANTIPIRETIK PADA MENCIT (Mus musculus) - Wanda Qoriasmadillah; Nirwana Haqiqi; Zuhratul Iman; Tri Wahyu Setyaningrum; Dining Aidil Candri; Andri Frediansyah; Eka Sunarwidhi Prasedya (Jurnal Penelitian Pendidikan IPA, 2024)
The Sasak tribe, who are the indigenous inhabitants of Lombok Island, use banten (Lannea coromandelica (Houtt.) Merr.) leaves as a medicinal plant to reduce fever. Fever is a physiological response to infection, characterized by a body temperature above the normal range of approximately ± 37 ℃. If left untreated, fever can cause dehydration, lack of oxygen, nerve damage, dizziness, decreased appetite, weakness, and muscle pain. To minimize these effects, antipyretics such as paracetamol can be used. However, prolonged or excessive use of paracetamol can cause hepatotoxicity, hepatic necrosis, renal tubular necrosis, and hypoglycemic coma.  Therefore, it is necessary to develop alternative herbal medicines to treat fever. The aim of this study is to determine the content and antipyretic effect of banten leaf extract, which was obtained through ethanol extraction. The antipyretic ability test utilized five groups: the negative control group, positive control group, and test groups receiving doses of 1 mg/25gBB, 3 mg/25gBB, and 10 mg/25gBB of ethanol extract of banten leaves. Fever induction was induced using the DPT-HB vaccine. The study found that the ethanol extract of banten leaves contained flavonoids (572.38 mg QE/gram extract), phenols (200.82 mg GAE/gram extract), and antioxidants (2.5063 mg GAE/gram extract with DPPH). The percentage of antioxidant inhibition in banten leaves between 9.68-47.16 %. Additionally, all test groups of the ethanol extract of banten leaves exhibited antipyretic activity. The antipyretic effect of the 3 mg/25gBB dose was equivalent to that of paracetamol. Similarly, the antipyretic effect of the 10 mg/25gBB dose was almost identical to that of paracetamol at 5 hours after treatment.